Using course journals to encourage reflective practice in second language teacher education. Issue 1 (2nd January 2021) - Barber, Jared David
ABSTRACT: This paper describes how the head of a second language teacher education program uses a course journals assignment to encourage reflective practice. Students in training to become second language teachers often report on a gap between the theory they learn in training programs and the pedagogical practice they implement in the field. Reflective practice in teaching has been shown to help new teachers to overcome this gap. To encourage students to develop a habit toward reflective practice, the head of this program has implemented a semester-long reflective journal assignment in a capstone course. Students report that the journal is engaging and effective in aiding them to develop their reflective abilities. This paper details the use of these course journals with the goal of encouraging more educators of future language educators to implement them as well.